2016
DOI: 10.1111/php.12579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Narrow‐band IR‐A and of Water‐Filtered Infrared A on Fibroblasts

Abstract: Exposures of the skin with electromagnetic radiation of wavelengths between 670 nm and 1400 nm are often used as a general treatment to improve wound healing and reduce pain, for example, in chronic diabetic skin lesions. We investigated the effects of water-filtered infrared A (wIRA) and of narrow-band IR-A provided by a light-emitting diode LED (LED-IR-A) irradiation in vitro on 3T3 fibroblast cultures under defined conditions with and without glyoxal administration. Glyoxal triggers the formation of advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…We hypothesized that since HCjE is a healthy cell line, they are probably more susceptible to stressors than cell lines from a cancerous origin such as HeLa, possibly explaining the slight viability decrease after irradiation with wIRA alone. A recent study supports our findings, stating that metabolic activity was even enhanced after wIRA irradiation in another continuous cell line (47). Knels Interestingly, in cultures infected with only MOI 0.1, irradiation with wIRA/VIS decreased the chlamydial infectivity more efficiently than wIRA alone.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We hypothesized that since HCjE is a healthy cell line, they are probably more susceptible to stressors than cell lines from a cancerous origin such as HeLa, possibly explaining the slight viability decrease after irradiation with wIRA alone. A recent study supports our findings, stating that metabolic activity was even enhanced after wIRA irradiation in another continuous cell line (47). Knels Interestingly, in cultures infected with only MOI 0.1, irradiation with wIRA/VIS decreased the chlamydial infectivity more efficiently than wIRA alone.…”
Section: Discussionsupporting
confidence: 90%
“…Knels et al recently discovered that wIRA irradiation of fibroblast cultures not only enhances metabolic activity, but also that it has a protective effect on cells, improving their viability under oxidative stress. The authors consider a possible beneficial effect on mitochondria (47).…”
Section: Discussionmentioning
confidence: 99%
“…The cells are well characterized and more easily cultured than the primary cells. For example, Knels et al recently reported the beneficial effects of infrared A on 3T3 fibroblast culture, which was regarded as a well‐defined cell line with a standard, stable growth rate . An additional argument given in favour of using the 3T3 cell line is that it is a globally accepted cell line for use in the neutral red uptake assay (NRU), which is a standardized method for acute toxicity testing in rodents .…”
Section: Discussionmentioning
confidence: 99%
“…The utility of the 3T3 cell line has been shown in many other biological and toxicological studies, using various experimental approaches. For example, 3T3 fibroblasts have been selected for the following purposes: 1/investigating the activity of bacterial toxins, antioxidants and cytokines, 2/evaluating the toxicity of drugs, e‐waste leachate, nanomaterials and nanoparticles or 3/studying the beneficial effects of electromagnetic radiation in living cells . These cells can also serve as a tool for the verification and validation of techniques assessing mitochondrial toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…However, wIRA-treatment restored original cell morphology in foreskin fibroblasts, and beyond that, collagen type I synthesis and TGF-β1 secretion in keloid fibroblasts [ 32 ]. Knels et al evaluated wIRA for the treatment of oxidative stress in cells as it is found in elderly or diabetic patients [ 33 ]. Therefore, they exposed fibroblast cultures to glyoxal to induce glycation of proteins and lipids, mimicking the conditions of oxidative stress, and determined their rescue from apoptotic death by wIRA.…”
Section: Introductionmentioning
confidence: 99%